Diagnosing onset of labor: a systematic review of definitions in the research literature - Hanley, Gillian E. (BMC Pregnancy Childbirth, 2016)
BACKGROUND: The diagnosis of labor onset has been described as one of the most important judgments in maternity care. There is compelling evidence that the duration of both latent and active phase labor are clinically important and require consistent approaches to measurement. In order to measure the duration of labor phases systematically, we need standard definitions of their onset. We reviewed the literature to examine definitions of labor onset and the evidentiary basis provided for these definitions. METHODS: Five electronic databases were searched using predefined search terms. We included English, French and German language studies published between January 1978 and March 2014 defining the onset of latent labor and/or active labor in a population of healthy women with term births. Studies focusing exclusively on induced labor were excluded. RESULTS: We included 62 studies. Four ‘types’ of labor onset were defined: latent phase, active phase, first stage and unspecified. Labor onset was most commonly defined through the presence of regular painful contractions (71 % of studies) and/or some measure of cervical dilatation (68 % of studies). However, there was considerable discrepancy about what constituted onset of labor even within ‘type’ of labor onset. The majority of studies did not provide evidentiary support for their choice of definition of labor onset. CONCLUSIONS: There is little consensus regarding definitions of labor onset in the research literature. In order to avoid misdiagnosis of the onset of labor and identify departures from normal labor trajectories, a consistent and measurable definition of labor onset for each phase and stage is essential. In choosing standard definitions, the consequences of their use on rates of maternal and fetal morbidity must also be examined.